Brewing Knowledge and Revenue: Coffeeshop Management in Higher Education Settings through Business Model Canvas - Fang, Liem Shiao; Singgalen, Yerik Afrianto (Forum Kerjasama Pendidikan Tinggi, 2025)
This research examines the integration of coffeeshop management into higher education curricula through Business Model Canvas methodologies, utilizing Le Café at Atma Jaya Catholic University of Indonesia as a case study. The investigation employs qualitative methodology, incorporating document analysis and participant observation, to evaluate the dual-purpose paradigm of campus-based coffee establishments functioning simultaneously as commercial enterprises and experiential learning laboratories. Findings reveal a bifurcated operational framework with distinct yet complementary value propositions: commercial hospitality services for campus stakeholders and authentic skill development opportunities for tourism students. Financial analysis demonstrates a significant maturation trajectory, with operations transitioning from consistent deficits in 2022-2023 to substantial surpluses exceeding Rp 20 million in late 2024, achieved through strategic revenue diversification across café operations (60%), consignment arrangements (20%), and event services (15%). The research identifies unique pedagogical advantages emerging from this educational-commercial integration, including enhanced practical competency development in areas traditionally challenging to address through conventional instruction. The study further establishes critical success factors for governance structures, including proportional resource allocation, integrated quality assurance protocols, and cross-functional oversight mechanisms. This comprehensive analytical framework contributes substantively to educational enterprise management literature while providing higher education institutions with implementable models for balancing academic rigor with commercial sustainability amid increasing financial constraints in contemporary educational environments.